An Investigation of Socially Sustainable Behaviour of Local Players in the Supply Chain of Shea Butter in Rural Borgu Nigeria: From a Role Theory Perspective - Sidikat, Shitu; Popoola, Oluwatoyin Muse Johnson (OMJP Alpha Publishing, 2017)
The Shea butter industry in Nigeria is fragmented, private-driven and less regulated. This paper explores the roles, practices, and behaviour of local supply chain stakeholders who mainly consist of rural women entrepreneurs that engage in Shea nut picking and Shea butter processing. Also, the research examines the local buying agents (LBA) who serve as the middlemen between the rural women and the exporters of Shea butter. This study deploys qualitative research design, guided by the Role theory. The study reveals that the rural women and the local buying agents are the key stakeholders who participate in the agricultural supply chain. Granting the fundamental principle of the sustainable supply chain, the findings indicate that the present active engagement and practices of these local stakeholders do not align with the principles of the sustainable supply chain. The study also exposes that factors such as gender disparity, weak access to financial support, and information asymmetry are major contributors to the present roles, practices, and behaviour of the local actors. The current study, therefore, put forward several recommendations to the Nigerian Government to encourage the construction of sustainable engagement and sustainable supply chain in the rural supply chain network